Opera and Freemasonry: The Funeral Canticle of José María Velásquez - López Maya, Juan de Dios (2016)
Cántico Fúnebre is a musical piece for tenor and orchestra written by nineteenth century Venezuelan composer Jose Maria Velasquez with lyrics by the politician and writer Francisco Conde. Cántico was written for the funeral of Juan Jose Conde, an independence leader and one of the founders of the local Masonry. The particular features of this piece are its remarkable influence of opera and the Masonic symbolism in the poem. This article provides, in first place, a vision of opera in Latin America and its use as a tool to emulate European culture. Then the process is studied by which the opera was penetrating the Masonic ritual until fully manifest in the funeral ceremony and finally, how the ruling elites, composed mostly of members of the order and the middle classes, adopted the opera as one of their main cultural values.